Triazole resistance prevalence in Aspergillus fumigatus in Mexico and Peru - Resendiz-Sharpe, Agustin (2019)
Introduction: Triazole-antifungal treatment, the recommended first-line therapy for aspergillosis, is threatened as triazole-resistance reports in Aspergillus fumigatus increase worldwide. Infection by resistant isolates not only occurs during prolonged triazole-treatments but also by inhalation of triazole-resistant spores from the environment. Modifications to the recommended initial triazole antifungal therapy have been proposed by an international expert consensus in centers with >10% environmental-resistance. However, triazole-resistance prevalence is not known in most countries as susceptibility testing is not routinely performed.Objective: To determine the prevalence of environmental triazole-resistant A. fumigatus in two Latin American countries, Mexico and Peru.Methodology: Environmental sampling. Triazole-resistance screening. Triazole-resistance confirmation.Results: A total of 304 soil samples were analyzed. Screening of environmental triazole-resistant A. fumigatus in Mexico and Peru.Conclusions: For the first time, triazole-resistant A. fumigatus was detected in soil samples in Mexico and Peru with a resistance prevalence of 6.9% and 9.8% respectively among A. fumigatus positive samples. Our findings emphasize the need to perform resistance screening or surveillance in clinical settings in these countries.